2019
DOI: 10.1039/c9cy01426h
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous MnO2 surviving calcination: an efficient catalyst for ozone decomposition

Abstract: Calcination at 300 °C of amorphous MnO2 maintains the structure and results in superior stability owing to the enhanced water-resistant ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 58 publications
0
33
0
Order By: Relevance
“…[ 516 ] Manganese oxides especially MnO 2 , are the most frequently studied catalytic materials for O 3 elimination. [ 168,283,371,517–523 ]…”
Section: Environmental Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 516 ] Manganese oxides especially MnO 2 , are the most frequently studied catalytic materials for O 3 elimination. [ 168,283,371,517–523 ]…”
Section: Environmental Applicationsmentioning
confidence: 99%
“…The researchers have found that amorphous MnO 2 , [ 522 ] α‐MnO 2 , [ 168,517 ] birnessite‐type MnO 2 , [ 524,525 ] δ‐MnO 2 , [ 526 ] γ‐MnO 2 , [ 519,527 ] and ε‐MnO 2 [ 528 ] have all shown superior O 3 ‐removal performances. Zhang et al.…”
Section: Environmental Applicationsmentioning
confidence: 99%
“…The active components of the catalyst mainly include noble metals [13][14][15] and transition metal oxides. [16][17][18][19] Imamura et al reported that p-type semiconductors have higher decomposition efficiency for ozone than n-type semiconductors. 20 Oyama measured the conductivity of the catalyst by the Hall effect and compared the correlation between oxide activity and conductivity, thereby further conrming that the p-type semiconductor oxide has higher activity for the catalytic decomposition of ozone.…”
Section: Introductionmentioning
confidence: 99%
“…prepared a series of amorphous MnO 2 nanoparticles through the calcination process for ozone decomposition and the crystallinity was regulated through different varying temperatures. [ 65 ] They reported that calcination temperature has an odd significant effect on morphology, texture, and surface chemistry of MnO 2 and MnO 2 nanoparticles calcined at 300°C (MnO 2 ‐300) exhibits superior electrocatalytic activity for ozone decomposition that is due to large surface area and high OV's. [ 65 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 65 ] They reported that calcination temperature has an odd significant effect on morphology, texture, and surface chemistry of MnO 2 and MnO 2 nanoparticles calcined at 300°C (MnO 2 ‐300) exhibits superior electrocatalytic activity for ozone decomposition that is due to large surface area and high OV's. [ 65 ]…”
Section: Introductionmentioning
confidence: 99%